Pengosongan Payudara dengan Pompa ASI Meningkatkan Produksi ASI Ibu Bekerja - Vinydea, Yosi Irlinta; Syiska Atik M; Karnasih, I Gusti Ayu; Ilmah Fakhriza (Indonesian Health Issue, 2025)
Background: Breastfeeding mothers often face a lack of milk production due to factors like changes in diet when returning to work and not breastfeeding or pumping frequently. In a previous study conducted at Arjasa Public Health Center, 100% of respondents reported inadequate milk production. Purpose : This study aims to analyze the effect of breast emptying using a breast pump on milk production in the Arjasa area. Methods: This study used a posttest-only control group design with 34 respondents, 17 in the control group and 17 people in the treatment group. Data were collected through a questionnaire and analyzed using the independent t-test statistical technique. Results: Independent t-test showed that the p-value was 0.001 < α = 0.05, leading to H0 rejection and Ha acceptance. This indicates that breast emptying using a breast pump affects breast milk production in working mothers in the Arjasa Community Health Center area. Conclusion: Breast emptying using a breast pump increases milk production. This increases prolactin hormone levels, the more milk emptied, the more milk produced. Thus, educating and supporting breastfeeding mothers in using a breast pump properly and the benefits of breast emptying is crucial for optimizing milk production.